AN EMPIRICAL RESEARCH OF CONSUMER EXPERIENCES OF FRESH-PRODUCT E-COMMERCE PLATFORMS: BASED ON TIME, CONVENIENCE AND PERCEIVED PRICE, EXEMPLIFIED BY COMMUNITY GROUP SHOPPING - Sun, Shiyu; Sun, Audrey (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2025)
This paper examines the consumer experiences of representative E-commerce platforms for fresh products and groceries in mainland China using the framework of the nine factors of business activities. The paper breaks down the analysis into three major attributes of consumer experiences: waiting time, convenience and perceived price level, which isolate the specific factors that affect consumer behaviour and, hence, the channels in which E-commerce managers could engage to improve their performances. This paper summarises the consumer experience by conducting anonymised large-scale online questionnaires and analyses the empirical data using descriptive statistics. The paper has spotted the shortcomings and inefficiencies in the operation of these e-commerce platforms and proposed targeted optimisation strategies to improve consumer experiences based on the empirical evidence and justified their feasibility. This paper aims to benefit both sides of the online grocery market by delivering more affordable prices and greater satisfaction to consumers and improved brand loyalty and core competitiveness to the E-commerce companies.